Effect of Farmyard Manure Seed Priming on Germination and Growth of Spinach (Spinacia oleracea L.) (Journal of Agriculture and Biology, 2025)
Spinach production is often constrained by poor seed germination and excessive reliance on chemical fertilizers, while the potential of organic seed priming, particularly with farmyard manure, to enhance seedling establishment and growth remains largely underexplored. A study was conducted at the Department of Horticulture, Sindh Agriculture University, Tandojam, during the winter season of 2024-2025 to investigate the impact of farmyard manure (FYM) seed priming at different concentrations on the germination and growth of spinach (Spinacia oleracea L.). The experiment was laid out in a Completely Randomized Design (CRD) with three replications. The treatments included: different concentration levels of farmyard manure. T0 = Control (unprimed seeds) T1 = Hydropriming (Distilled water), T2 = 1% FYM T3 = 10% FYM, T4 = 20% FYM, T5 = 30% FYM. The results showed that seeds primed with 30% FYM resulted in the maximum values for all parameters, including seed germination (18.60%), germination index (5.96), number of leaves per plant (24.87), plant height (26.38 cm), plant fresh weight (17.75 g), shoot fresh biomass (14.24 g), root fresh biomass (3.38 g), shoot dry biomass (2.52 g), and root dry biomass (1.44 g). In contrast, the lowest seed germination percentage (11.30%) and germination index (3.05) were recorded in the 10% FYM treatment (T3). Hydropriming (T1) resulted in the lowest values for several growth parameters, including the number of leaves per plant (13.77), plant height (17.95 cm), shoot fresh biomass (4.40 g), and root dry biomass (0.10 g). Meanwhile, the control treatment (T0) produced the lowest plant fresh weight (5.52 g) and fresh root biomass (1.13 g). In conclusion, seed priming with 30% farmyard manure significantly enhanced the germination and growth performance of spinach and is recommended over hydropriming as well as lower FYM concentrations.